Chest X-Ray pattern and lung severity score in COVID-19 patients with diabetes mellitus: A cross sectional study - Aswin Gunawan Christanto; Dian Komala Dewi; Harry Galuh Nugraha; Irma Hassan Hikmat (Elsevier, 2022)
Background: Diabetes mellitus is a chronic hyperglycemic condition that can affect the body's immune response to SARS-CoV-2 This study aimed to determine the relationship between diabetes mellitus and lung severity in COVID-19 patients. Methods: A cross-sectional design was conducted at Hasan Sadikin General Hospital during the January-May 2021 period. Data were based on medical records of patients aged 18 years and over with COVID-19. The chi-square test was performed to assess the relationship between diabetes mellitus and lung severity based on the BRIXIA score. Results: This study included 538 subjects, mostly aged <60 years (71.9%) and female (60.2%). A total of 125 subjects had abnormal blood glucose levels with an average HbA1c of 9.00 ± 1.77% in patients with diabetes mellitus and a median HbA1c of 5.85% (4.5-6.4%) in patients with reactive hyperglycemia. Lung abnormalities were found in 357 subjects (66.4%). The results of the BRIXIA score to assess lung severity found as many as 77 subjects (14.3%) had a score of 11-18 with 14 people with diabetes mellitus, five people with reactive hyperglycemia. In the population aged ≥60 years, as many as 32 people had a score of 11-18 with three people with diabetes mellitus, two with reactive hyperglycemia and 27 with normal blood glucose. A significant relationship was found between diabetes mellitus and lung severity (p = 0.024). Conclusion: There is a significant relationship between diabetes mellitus and lung severity in COVID-19 patients aged ≥60 years.